Has the Chinese economy become more sensitive to interest rates? Studying credit demand in China - Tuuli Koivu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
Chinese authorities have traditionally relied mainly on administrative and quantitative measures in conducting monetary policy, with interest rates playing a less prominent role. Additional support for this view resides in a number of earlier studies that have found that the impact of interest rates on the real economy has been miniscule. However, taking into account numerous reforms in the financial sector and more widely in the Chinese economy, interest rates may have gained some influence in the last few years. It is important to study the effectiveness of interest rates also in light of future reforms of the monetary policy tools in China. Whereas administrative policy measures were effective in guiding the behaviour of state-owned enterprises, the authorities may need to increase the use of more market-oriented monetary policy tools as the share of the economy in private and foreign ownership grows. We use a vector error correction model to study, within a credit demand framework, whether the impact of interest rates in China has become stronger over the last decade. Our results suggest that loan demand has indeed become more dependent on interest rates. albeit the channel from interest rate to the real economy is still weak.
URN:NBN:fi:bof-201408072065
Keywords: E52; P24; 330; China; monetary policy